2004
DOI: 10.1110/ps.04926604
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of side chain mobility among protein G B1 domain mutants with widely varying stabilities

Abstract: Abstract"Host-guest" studies of the B1 domain from Streptococcal protein G have been used previously to establish a thermodynamic scale for the ␤-sheet-forming propensities of the 20 common amino acids. To investigate the contribution of side chain conformational entropy to the relative stabilities of B1 domain mutants, we have determined the dynamics of side chain methyl groups in 10 of the 20 mutants used in a previous study. Deuterium relaxation rates were measured using two-dimensional NMR techniques for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…The chemical shift differences were not simply a result of the chemical differences between the model system and the full-length protein in its amyloid form. Characterization of a variety of mutated forms of the B1 domain of protein G revealed that the average changes in chemical shift from a nonstructurally perturbative mutation are small (∼0.1 ppm in 13 C and 0.3 ppm in 15 N) (40). The one-bond TEDOR spectrum of a uniformly 13 C-and 15 N-labeled NM fiber sample at room temperature (A) is greatly simplified by using an NM molecule that is isotopically labeled at only the first 14 amino acids (B) (red).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical shift differences were not simply a result of the chemical differences between the model system and the full-length protein in its amyloid form. Characterization of a variety of mutated forms of the B1 domain of protein G revealed that the average changes in chemical shift from a nonstructurally perturbative mutation are small (∼0.1 ppm in 13 C and 0.3 ppm in 15 N) (40). The one-bond TEDOR spectrum of a uniformly 13 C-and 15 N-labeled NM fiber sample at room temperature (A) is greatly simplified by using an NM molecule that is isotopically labeled at only the first 14 amino acids (B) (red).…”
Section: Resultsmentioning
confidence: 99%
“…In a “typical” analysis, values of τ f and are extracted from fits of R 1 , R 2 rates to the model described above, eqs 1–3, assuming a value for τ C that is obtained from backbone 15 N spin relaxation experiments [36], [47][49]. Here we have taken a different strategy that avoids complications that emerge from a potentially erroneous τ C value resulting from 15 N relaxation rates “contaminated” by chemical exchange.…”
Section: Resultsmentioning
confidence: 99%
“…The proteins used in this study are: ubiquitin (PDB id: 1UBQ) 43 , the third fibronectin type III domain from human tenascin (TNfn3; PDB id: 1TEN) 44 , the tenth fibronectin type III domain from human fibronectin (FNfn10; PDB id: 1FNA) 45 , the B1 domain from protein G (gb1; PDB id: 1PGB) 46 , the SH3 domain in human Fyn (fyn-sh3; PDB id: 1SHF) 34 , the de novo designed three-helix bundle α3D (a3D; PDB id: 2A3D) 6 , eglin c (PDB id: 1CSE) 7; 47 , an SH2 domain of phospholipase C-gamma1 (plcc-sh2; PDB id: 2PLD) 7 , the B1 domain of protein L (proteinL; PDB id: 1HZ6) 31 , HIV-1 protease homodimer bound to the inhibitor DMP323, (hiv-protease-holo; PDB id: 1QBS), flavodoxin bound to flavin mononucleotide (flavodoxin-holo; PDB id: 1OBO) 48 , cytochrome c2 bound to its heme prosthetic group (cytochrome-c2-holo; PDB id: 1C2R) 49 , the N-terminal domain of chicken skeletal troponin C (NTnC; PDB id: 1AVS) 50 , Cdc42Hs 51 , adipocyte lipid-binding protein (albp; PDB id: 1LIB) 52 , muscle fatty acid-binding protein (mfabp; PDB id: 1HMT) 52 , and Ca 2+ -loaded calmodulin (PDB id: 1AHR) 53 .…”
Section: Dataset Of Experimental Protein Structures and Relaxation Mementioning
confidence: 99%